Examination of the need for treatment and the variables affecting survival in patients with chronic lymphocytic leukemia without indication for treatment at admission - Dogan, Esma Evrim; Demirel, Naciye; Aydin, Demet; Eren, Rafet (Annals of Medical Research, 2022)
Abstract Aim: To evaluate the clinical features of patients with early-stage chronic lymphocytic leukemia (CLL) without any indication for treatment, and to examine the effects of features recorded during diagnosis on the need for treatment and the predictability of survival without treatment. Materials and Methods: This study was conducted by retrospectively evaluating the files of 53 patients with early-stage CLL who attended follow-up in the hematology outpatient clinic of Okmeydanı Training and Research Hospital, between 2000 and 2019, and who had no indication for treatment at the time of diagnosis. The sociodemographic characteristics of the patients, blood values recorded at diagnosis, physical examination findings, disease stage (Binet and Rai staging), immunophenotypic findings, and treatment characteristics were examined. Results: Of the 53 patients whose results were evaluated, 28 (52.8%) were women and the mean age was 62.96 ± 9.30 years. According to the Binet staging at the time of diagnosis, 43 (81.1%) patients were Binet A and 10 (18.9%) were Binet B. According to Rai staging, 22 (41.5%) patients were Rai 0, 19 (35.8%) were Rai 1 and 12 (22.6%) patients were Rai 2. Treatment was required in 10 (18.9%) patients during follow-up. The leukocyte count and lymphadenopathy count of the patients who received treatment were significantly higher (p = 0.022, p = 0.007, respectively). Twenty-two (51.2%) patients who did not receive treatment were Rai 0; there was no patient with Rai 0 among those who received treatment. Multivariable logistic regression analysis was performed to determine significant parameters associated with receiving treatment, and Rai stage (OR: 4.683, 95% CI: 1.548-14.172, p = 0.006) was found to be significant. Survival without treatment was not associated with sex, age, splenomegaly, hepatomegaly, lymphadenopathy, Binet stage, Rai stage, and CD38-positivity (p > 0.05). Conclusion: In patients with early-stage CLL who do not need treatment at the time of diagnosis, possible need for treatment may be associated with Rai stage.